Rural Potential, Food Security, and Poverty: A Study in Batu City, East Java - Setyo Tri Wahyudi; Rihana Sofie Nabella; Kartika Sari (MediaTrend, 2021)
This study aims to analyze the potential of rural areas and the linkage of rural potential in an effort to increase food security and alleviate poverty. East Java has great potential as a support for national food security, but the number of people living below the poverty line is the largest in Indonesia, one of which is in Batu City. This research uses a descriptive method. The results showed that each village in Batu City has various agricultural potentials and the majority of the population works in the agriculture and tourism sector. Based on the results of the analysis, it was found that the superior commodity farmers in Batu had opportunities, namely productivity, socialization and training from the government. However, business actors also face obstacles in the form of weather, capital and marketing factors.